Impact of air pollution on respiratory microbiome: A narrative review. (February 2023) - Vieceli, Tarsila; Tejada, Sofia; Martinez-Reviejo, Raquel; Pumarola, Tomas; Schrenzel, Jacques; Waterer, Grant W.; Rello, Jordi
Highlights: Air pollution, measured in different ways, is associated with microbiome changes and increased pathogen carriage in different populations. A shift towards colonizing bacteria may expose ventilated patients to higher risk of nosocomial infection by organisms with multidrug resistance. Use of probiotics may restore the diversity of baseline microbiome, preventing infections by resistant organisms in the critical care setting. Using protective equipment decreased the effect of air pollutants on increasing potentially pathogenic microorganisms. Abstract: Background: Respiratory microbiome composition depends on an intricate balance between host characteristics, diet, and environmental factors. Some studies indicate a bidirectional relationship between respiratory microbiota and disease. Air pollution is consistently associated with increased respiratory morbidity and mortality in different populations and across different ages. The aim of this review was to report a summary of the evidence regarding the impact of air pollution on the upper and lower respiratory tract microbiome. Methods: A literature search from interaction between air pollution and respiratory microbiome was performed (2010–2022). Results: Sixteen studies demonstrated changes in microbiome with both environmental and household air pollution. Increasing levels of air pollutants are associated with lower relative abundance of Corynebacterium and increasing levels of pathogen colonization, such as Haemophilus influenzae, Moraxella catarrhalis, Streptococcus pneumoniae and Pseudomonas aeruginosa and Acinetobacter baumannii, altering the incidence and clinical course of respiratory infections. This ultimately leads to an excess of morbidity and mortality due to antimicrobial resistance. Conclusion: Changes of air pollution on the respiratory microbiome may influence respiratory infections in critical care. Use of probiotics may restore the diversity of baseline microbiome, preventing infections by resistant organisms in the critical care setting. Using protective equipment decreased the effect of air pollutants on increasing potentially pathogenic microorganisms.